Peran Government Support dan Social Capital Terhadap Kinerja Usaha UMKM Kabupaten Pasuruan Melalui Motivasi Wirausaha - Mukhamad Nanang Mahbuby; Antin Rakhmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Business performance is a key factor in determining business sustainability and growth, especially for Micro, Small, and Medium Enterprises (MSMEs). This productivity is influenced by various internal and external factors, including government support, social capital, and entrepreneurial motivation. This study aims to analyze the effect of government support and social capital on business performance through entrepreneurial motivation in Pasuruan Regency. Government support in the form of capital assistance, business training, and regulatory simplification contributes to increasing MSME productivity. Social capital, which reflects social networks, trust, and collaboration in the business community, also plays an important role in expanding access to resources and business opportunities. Entrepreneurial motivation is an intermediary factor that connects government support and social capital with business performance, where entrepreneurs who have high motivation tend to be more innovative and adaptive to challenges.